Analysis of Sumatran Orangutan (Pongo abelii) Food Tree Species Based on Variations in Altitude at Ketambe Research Station - Taufiq Nurcholisudin; Muslich Hidayat; Anton Widyanto (UIN Sulthan Thaha Saifuddin Jambi, 2024)
Orangutans are a key species in biodiversity that is vital for ecosystem balance. However, the Sumatran Orangutan (Pongo abelii) population is declining due to habitat loss and the reduction of important food trees. This study aims to identify the types of food trees and tree parts consumed by Sumatran Orangutans based on height. Conducted at Ketambe Research Station, the results of the study are presented in the form of posters and teaching materials for reference. Exploratory survey method using line transects at three altitude strata (300-600 masl, 600-900 masl, and 900-1100 masl) with purposive sampling based on the presence of food trees and slope conditions. Data were collected through observation sheets and analyzed descriptively. The findings showed 50 species of food trees at 300-600 masl (60.24%), 34 species at 600-900 masl (40.96%), and 38 species at 900-1100 masl (45.78%). Tree parts consumed include fruits (81.9%), seeds (7.2%), young leaves (1.2%), flowers (1.2%), and various combinations of tree parts. This study is expected to broaden the understanding of Sumatran orangutan food tree species at various altitudes and provide important data for the management of Ketambe Research Station.